Studi Komparatif Bahasa Jurnalistik Advertorial pada Media Online Detik.com dan Kompas.com - Ine Fitrianingsih; Qanitah Salma; Meiby Zulfikar; Siti Abelia Puteri; Lapina Lena; Della Meira; Rini Sartika (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze and compare the advertorial writing styles of two major Indonesian online media outlets: Detik.com and Kompas.com. Using a qualitative descriptive approach, the study examines the text structure, use of journalistic language, and application of the 5W+1H elements in each media’s advertorials. The analysis reveals that Detik.com tends to employ longer, information-dense, and technical sentences, while Kompas.com uses a more formal, informative, and concise writing style. These differences reflect the editorial strategies and target audience segmentation of each media outlet. This research contributes to the field of mass communication by providing insights into the dynamics of advertorial content as a hybrid form between journalism and marketing.